2004
DOI: 10.1111/j.1365-2621.2004.tb10705.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection Properties of Irradiated Ostrich Meat by DNA Comet Assay and Radiation‐induced Hydrocarbons

Abstract: Detection of irradiated ostrich meat with doses of 1 to 10 kGy using the DNA comet assay and hydrocarbon determinations by gas chromatography-mass spectrometry was investigated. The irradiated ostrich meat showed comets with long tails whereas nonirradiated controls showed intact cells only slight comets. Concentrations of radiation-induced hydrocarbons increased with irradiation dose. Radiation-induced hydrocarbons in ostrich meat were detected at doses of 1 kGy or more; however, they were not detected in non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
(7 reference statements)
1
1
0
Order By: Relevance
“…The results showed that while irradiated cells had comets with long tails, nonirradiated cells showed no tail or very short ones, and the shape of comets depended on the irradiation doses (Figure 8). Chung and others (2004) also reported a similar result for irradiated ostrich meat with doses of 1 to 10 kGy. The irradiated ostrich meat showed comets with long tails, whereas nonirradiated samples with intact cells showed only slight comets.…”
supporting
confidence: 57%
“…The results showed that while irradiated cells had comets with long tails, nonirradiated cells showed no tail or very short ones, and the shape of comets depended on the irradiation doses (Figure 8). Chung and others (2004) also reported a similar result for irradiated ostrich meat with doses of 1 to 10 kGy. The irradiated ostrich meat showed comets with long tails, whereas nonirradiated samples with intact cells showed only slight comets.…”
supporting
confidence: 57%
“…Table 6. Radiation induced C n-1 -and C n-2:1 -hydrocarbons and 2-alkylcyclobutanones produced from the major fatty acids (FA) in food The amount of C n-1 -and C n-2:1 -hydrocarbons in irradiated chicken, pork, beef and ostrich meat is in the range of 0.05 to 0.9 µg/g fat/kGy (Chung et al, 2004;Morehouse and Ku, 1993;Nawar et al, 1990;Sjoberg et al, 1990).…”
Section: Hydrocarbonsmentioning
confidence: 99%